Genetic structure and essential oil diversity of the aromatic shrub Lippia origanoides Kunth (Verbenaceae) in two populations from northern Colombia - Nelson Enrique Vega-Vela (Agronomía Colombiana, 2013)
In the present study, the diversity in essential oil composition and genetic structure of two populations of Lippia origanoides from Colombia, one from the department of Magdalena on the Atlantic coast in the north, and the other from the canyon of the Chicamocha river in the northeast, were compared. Individuals were sampled in each of the two populations and ISSR (inter-simple sequence repeat) molecular markers were applied to document the distribution of the genetic diversity within and among the populations. Essential oils were extracted by steam distillation from individuals collected in the two populations and analyzed by gas chromatography and mass spectrometry (GC-MS). The results suggest that genetic diversity levels of L. origanoides in Magdalena and Chicamocha are relatively high (Hs ranged from 0.35 to 0.37) and comparable to allogamous plant species and other related species of the same genus. A rather low genetic differentiation (qII varied from 0.07 to 0.17) was found between the two populations, in spite of the relatively large geographical distance between them. The essential oils of L. origanoides can be classified as monoterpenic in type, and according to the relative amount of the major compounds, six chemotypes are proposed. Five of them (B, C, D, F and G) are present in the canyon of the Chicamocha river, while two of them (C and E) are present in Magdalena. Chemotypes B and C are similar to chemotypes previously reported. In summary, the essential oils from individuals collected in Chicamocha are rich in thymol (chemotypes C and D); carvacrol (chemotype B); Ρcymene, eucalyptol (+ Β-phellandrene trace) and thymol methyl ether (chemotype F); and thymol methyl ether, pcymene, thymol and Υ-terpinene (chemotype G); while those from Magdalena are rich in thymol (chemotype C), and eucalyptol and α-phellandrene (chemotype E). These results suggest a significant presence of genetic and essential oil diversity in this species, which should be studied further in order to make more efficient use of this promising plant resource